Workplace Violence and Abuse Against Nurses in Hospitals in Iran - Mahnaz Shoghi, MSN; Mahnaz Sanjari, MSN; Fateme Shirazi, MSN; Shiva Heidari, MSN; Sedighe Salemi, MSN; Ghazanfar Mirzabeigi, BSN (Elsevier, 2008)
The rising rate of violence and abuse in health care centers has become a major problem for nurses. The purpose of this cross-sectional study was to explore the prevalence of assaults during nurses' careers in the Islamic Republic of Iran. Methods: Self-report questionnaires were filled out by 1,317 nurses. Results: Verbal abuse was experienced by 87.4% of the population during a 6-month period, and physical violence by 27.6% during the same period of time. No physical harm was reported in 66.4% of cases. Only 35.9% cases of verbal abuse and 49.9% cases of physical violence were actually reported. The majority of cases reported that abuse was followed by either inaction or by actions which failed to satisfy the victim. According to the findings, men were exposed to more abuse than women, and the risk of experiencing abuse was higher in nurses with more job experience or who worked more hours. Also, nurses who are responsible for first aid were subjected to more abuse than those in other positions. Conclusion: The findings showed a noticeable trend of a rising number of assaults against nurses. The findings of this study may help hospital staff and nurses to avoid, reduce and control violence and abuse.